Physiological causes of yield variation in similar durated mungbean genotypes (Journal of Bangladesh Academy of Sciences, 2023)
The experiment was conducted during February to May, 2019 at the research farm of Bangladesh Institute of Nuclear Agriculture, Mymensingh-2202. The objective of the study was to evaluate the growth, reproductive characteristics, yield and yield components of four similar durated mungbean genotypes, namely BARI Mung-2, Binamoog-2, MB-29, and MB-43. At most of the growth stages, the mutant MB-29 showed superiority in terms of growth parameters such as total dry matter, leaf area index, absolute growth rate, relative growth rate, and net assimilation rate whilst MB-43 showed the inferiority. Furthermore, MB-29 outperformed the other three genotypes in yield attributing features, resulting in a higher seed yield than the other three genotypes. In comparison, the MB-43 mutant showed the lowest value for the yield parameters. The seed yield correlated positively and significantly with leaf area, total dry matter, absolute growth rate, and number of pods plant-1.J. Bangladesh Acad. Sci. 47(1); 101-108: June 2023